Modeling Physical and Physiological Processes Reveals the Role of Turbulence in the Prerequisites for Microcystis Blooms - Na Li; Xueping Gao; Bowen Sun (Water Resources Research)
Abstract Harmful algal blooms of Microcystis have become a global problem. Turbulence, a determining factor affecting blooms, not only disperses surface scum but also controls the growth of Microcystis. Numerous studies have analyzed the effects of turbulence on the growth and colony size of Microcystis in laboratories, but the turbulence thresholds for Microcystis growth and colony disaggregation in the field are difficult to determine due to the complex environment. In addition, the quantitative contribution of turbulence‐driven blooms and the intrinsic mechanisms of the spatial distribution responding to turbulence are unclear. In this study, a fully integrated filed scale computational model focusing on turbulence‐driven blooms was developed, which incorporates physical processes (turbulence‐induced vertical mixing, VMT) and physiological processes such as buoyancy‐controlling transport (BCT), turbulence‐induced colony size variation (CSV), and growth rate variation (GRV). We performed model sensitivity analysis and evaluated the effects of turbulence intensity and duration on the biomass and vertical distribution of Microcystis. The results show that the optimal turbulence dissipation rate for Microcystis growth in the field is 1.0 × 10−5 m2/s3 and the critical turbulence dissipation rate for aggregation distribution is 3.81 × 10−6 m2/s3 in shallow lakes. A quantitative comparison of the effects of physical/physiological processes on blooms shows that physiological processes (CSV, GRV, and BCT) are critical for biomass enrichment, and the accumulation of Microcystis at the water surface is dominated by physical processes (VMT). This study reveals the mechanisms of turbulence‐driven Microcystis blooms and provides new insights for algal bloom prediction and control.